THE NEGOTIATIONS FOR PEACE IN SRI LANKA: ADVANCES AND SETBACKS - Antônio Duarte Santos, Gilberto (2024)
The civil war in Sri Lanka was caused by the discrimination of its largest ethnic minority, the Tamils, by its ethnic majority, the Sinhalese. In 1983, a rebel armed group, the Liberation Tigers of Tamil Eelam (LTTE) committed an attack which sparked the conflict. The conflict intensified in the 1990s, though the belligerents were exhausted by the early year 2000, when Norway mediated. There were several attempts at negotiation, parallel to the ongoing military confrontations. India imposed an unsuccessful mediation in the 1980s, and the Sri Lankan government attempted non-mediated talks during the 1990s. Norway mediated the conflict from 2000 to 2008, resulting in a Ceasefire Agreement. The ceasefire’s monitoring mechanism was flawed and the internationalisation of the peace process led to the mutual lack of confidence from the parts, which ended the process in 2008.